1996
DOI: 10.1111/j.1746-1561.1996.tb03393.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation in Illustrations, Text, and Topic Areas in Sexuality Education Curricula

Abstract: A content analysis instrument was developed to examine differences in gender representation in sexuality education curricula. Fourteen middle school and high school curricula, published between 1985 and 1995, were examined. Variables included illustrations, noun/pronoun usage, and specific topics within the two categories of biological function and mutual interest. The study examined differences in gender representation in illustrations, photographs, cartoons, drawings, and text. Omission of sexuality topics r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Evaluation of the extent to which textbooks on sexuality and human social ideology on the content of HIV/AIDS education (10), another identified gender representation and examined gender inequity in textbook descriptions (14).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of the extent to which textbooks on sexuality and human social ideology on the content of HIV/AIDS education (10), another identified gender representation and examined gender inequity in textbook descriptions (14).…”
Section: Methodsmentioning
confidence: 99%
“…The main health topics in 12 studies were sexuality, sexually transmitted diseases (STDs), and nutrition. Of the included studies, 4 focused on sexuality, including reproductive health, gender representation, and STDs (7,(13)(14)(15), 3 focused on nutrition or diet, including excessive intake of sugar-rich food (12,16,17), and 1 each focused on HIV/AIDS (10), mental health (18), hearing health (19), oral cancer (20), and vaccination (11). Two other Spanish studies identified the priorities of health topics covered.…”
Section: Specific Health Topics Coveredmentioning
confidence: 99%
“…swollen testicles), (Alt, 2001). Beyer et al (1996), argued that in middle and high school sexuality curricula that they had examined, males were represented as perpetrators of sexual exploitation, while females were portrayed as the victims of exploitation, abuse, assault and rape. Beyer et al (1996) researched fourteen United…”
Section: Gender Culture and Sexualitymentioning
confidence: 99%
“…It is of particular concern that gender inequalities and inequities may exist in school curricula that suppose to broaden knowledge and promote health. Further, gender role stereotyping in sexuality education curricula was noted by Beyer et al (1996), in relation to parenting which had a pro-feminine slant. The male role in parenting was omitted.…”
Section: Gender Culture and Sexualitymentioning
confidence: 99%
“…As curricular imperatives, both the overarching domain of ''the sexual'' and the niche of ''the sex education illustration'' are recognized zones of ideological rough-andtumble. However, pictures in sex education books are rarely examined (see, for example, Beyer, Ogletree, Ritzel, Drolet, Gilbert, & Brown, 1996;Hartlaub & Dreznick, 2001;Jackson & Gee, 2005;Low & Sherrard, 1999;Pollis, 1986;Salas, 2004;Whatley, 1988Whatley, , 1992. This is unfortunate, given the wealth of research opportunities for pictorial semioticians, visual historians, visual anthropologists, ethnologists, curriculum theorists, pedagogues, culture critics, gender activists, and discourse analysts working in the domains of law, pedagogy, and sexualities.…”
Section: Sex: Education Visual Access Stratificationmentioning
confidence: 99%